2022
DOI: 10.3389/fvets.2022.915956
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Transcription Profiles of Proliferating Bovine Ovarian Granulosa When Exposed to Increased Levels of β-Hydroxybutyric Acid

Abstract: Ketosis is common in high-yield dairy cows. It is a condition that is characterized by the accumulation of serum β-hydroxybutyric acid (BHBA). Both subclinical ketosis and clinical ketosis can compromise the reproductive performance and cause long-lasting negative effects on reproductive efficiency by affecting the proliferation of follicular and granulosa cells. However, the regulatory mechanisms involved in the development of follicular cells and granulosa cells in cows experiencing subclinical ketosis and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Herein, we detected an increase in the apoptotic rate of fGCs as well as pro-apoptoticrelated proteins with increasing BHBA concentrations. Similarly, in our previous study, we identified that the differentially expressed genes were involved in apoptosis pathway after 2.4 mmol/L BHBA stress [52]. This suggests that increased concentrations of BHBA-induced apoptosis in fGCs; this may be an impaired developmental factor of follicles.…”
Section: Discussionsupporting
confidence: 73%
“…Herein, we detected an increase in the apoptotic rate of fGCs as well as pro-apoptoticrelated proteins with increasing BHBA concentrations. Similarly, in our previous study, we identified that the differentially expressed genes were involved in apoptosis pathway after 2.4 mmol/L BHBA stress [52]. This suggests that increased concentrations of BHBA-induced apoptosis in fGCs; this may be an impaired developmental factor of follicles.…”
Section: Discussionsupporting
confidence: 73%
“…a Oral daily administration of propylene glycol (PG-OVS) or water (CON-OVS) during the Ovsynch protocol in lactating dairy cows. Gong et al, 2022;Vanholder et al, 2015). On the other hand, a decreased BHBA concentration can have a positive effect on steroid mechanisms, increasing the quality of oocytes and the ability of embryo development in dairy cows (Ospina et al, 2010;Pishvaei et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the relationship between BHBA concentrations and fertility is complex and may vary depending on the individual cow and the specific circumstances. It has been demonstrated that higher BHBA concentration impaired hypothalamic pituitary–ovarian axis, granulosa cell development, follicular steroidogenesis in granulosa cells and oocyte maturation (Butler, 2003; Gong et al, 2022; Vanholder et al, 2015). On the other hand, a decreased BHBA concentration can have a positive effect on steroid mechanisms, increasing the quality of oocytes and the ability of embryo development in dairy cows (Ospina et al, 2010; Pishvaei et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by the accumulation of serum ketone βHB. Both subclinical ketosis and clinical ketosis can compromise reproductive performance and cause long-lasting negative effects on reproductive efficiency ( Gong et al, 2022 ). In this study, we detected the effects of βHB on mitochondria functions and energy metabolism during bovine oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%